Marketing Influence on Membership Intention: The Role of Promotion and Word of Mouth in KSPPS Kospin Jasa Syariah Bulakamba - Ela Fitriyani; Moh. Mabruri Faozi; Rita Kusumadewi (CIEBER: Contemporary Islamic Economic and Business Review, 2026)
This study aims to analyze the effect of promotion and word of mouth on interest in becoming a member of KSPPS Kospin Jasa Syariah Bulakamba. This research uses a quantitative approach with a sample of 100 respondents. The population in this study were the people of Jubang Village. The results of this study indicate that partially the promotion variable has no significant effect on the interest in becoming a member of KSPPS Kospin Jasa Syariah Bulakamba. Meanwhile, the word of mouth variable partially has a significant effect on the interest in becoming a member of KSPPS Kospin Jasa Syariah Bulakamba. The results of the F test show that promotion and word of mouth have a significant effect on the interest in becoming a member of KSPPS Kospin Jasa Syariah Bulakamba with a simultaneous effect of 82.85%.